Salary in the system of financial motivation of staff ("Journal "U". Economy. Management. Finance.", 2024)
The article examines the current state of the system of financial motivation of personnel, namely, the organization of employee remuneration as one of the main components of this system. Additional methods and approaches of financial incentives for personnel are analyzed, as well as the principles of remuneration organization in developed countries of the world are considered.
Keywords: salary; staff motivation; average salary; median salary; labor efficiency